PROSES PEMBANGUNAN REPOSITORY INSTITUSI (STUDI KASUS PADA UIN MATARAM) - Nuraeni Nuraeni; Rika Kurniawaty (UIN Imam Bonjol Padang, 2019)
Institutional Repository is a tool or media to store and publish scientific works of Civitas in an institution, such as Papers, theses, journal articles, books, proceedings, teaching materials, and other scientific works, which can be accessed online and utilized by the society. In the early stages of the university repository's development, the things that need to be done are benchmarking, vision and missions assignment, and purpose of the repository, making supporting rules such as SOP, and preparation of facilities and infrastructures. Repository information processing activities can be initiated by digitizing collections or scientific-intellectual work already been in the library, submission of scientific works in digital form, as well as self-uploads. Once the system is running, it is necessary to strive for the action that the repository collection can still be accessed online. Such actions are by conducting maintenance (infrastructures and networking), network and server security, and conducting various socialization activities (promotion). The more visitor who access the repository link, cite or utilize the repository, it will increase the citation and webometric ranking of an institution.